First record for an alien oriental river prawn Macrobrachium nipponense (De Haan, 1849) (Decapoda, Palaemonidae) distribution in the lower Danube, Bulgarian part confirmed with DNA barcoding - Yordan Kutsarov; Petya Ivanova; Nina Dzhembekova; Violin Raykov; Elitsa Hineva; Elica Valkova; Kristian Yakimov (Nature Conservation)
The alien species Macrobrachium nipponense (De Haan, 1849), known as the oriental river prawn, has been identified in the Bulgarian part of the Lower Danube for the first time, based on morphological characteristics and DNA barcoding. Four specimens were caught in October 2023 in the Danube River near Pozharevo island (422.2 rkm). The diagnosis of the species was based on the number of the teeth on the dorsal and ventral side of the rostrum, the large size of the second pair of pereopods, and the presence of the hepatic spine. A fragment of cytochrome c oxidase subunit I (COI) gene of mitochondrial DNA was sequenced to supplement species identification. Phylogenetic analysis has revealed a high genetic similarity (over 99%) between the Bulgarian sample and samples from various geographic locations (Ukraine, China, Bangladesh, Iran, Iraq, and Russia). The record of the oriental river prawn confirms its expansion and successful naturalization in the Lower Danube region. The invasion of the species will probably affect the structure of benthic macroinvertebrate communities and represent a high risk to native species, which necessitates long-term monitoring of species’ impact on Danube River ecosystems.